Harmony As Ideology: Politics Among The Dutch Communitty In Solo, 1900-1915 - . Kuntowijoyo (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2002)
Small in number, the Dutch community in Solo, 1900-1915, enjoyed a splendid life. They had everything European at that time had. Jobs, technology, facilities, faith, and leisure time activities were all available for them. They were at ease with the local community. The Dutch style of life was partly adopted by the upper layer of the native. They were in harmony with the authorities (the Dutch administration and the two Javanese principalities: the Kasunanan and the Mangkunegaran) and the Javanese. When the Indische Party (IP) was established in 1912 in Bandung, they accepted the party but not the ideology of radicalism. They refused the idea of an independent state offered by the lerdership of IP, promoted instead an autonomy under the Dutch. In Solo they prefered an autonomy under the Dutch, because in fact they had lived in harmony with the Javanese, and reversely, the Javanese themselves looked happy with the Dutch, culturally and politically. When the IP was not legalized by the Government the IP Solo went to be a social and local organization. They would like to live harmoniously with the Javanese and the Dutch authority. Their ideology became clearer, they were populist and loyalist.